An Educational Program Evaluation on Fluid Mechanics Course Oriented Critical Thinking Skill - Diniya, Diniya (Madania: Jurnal Ilmu-Ilmu Keislaman, 2024)
A way to actualize an educators in universities is through lectures. The present study aims to evaluate the fluid mechanics through the CIPP model. Conducted through evaluative research at one of the universities in Pekanbaru, the data were collected through interviews, observation, questionnaires and documents. The current research employs interview guidelines, observation sheet, questionnaires and document review sheets. The data analysis technique uses the data triangulation model. Based on results obtained in this line of research, there are no specific skills listed in the SCP, there is one sub-CLO that does not disclose critical thinking skills. Based on lecture observations, only one student asked questions and presented the answers to the exercise questions. Based on the results of the questionnaires, it was found that 69.7% of students still have difficulties in the topic of Dynamic Fluids. Based on interviews, students still have difficulty in using formulas. The conclusion is that fluid mechanics still need improvement in the SCP design, especially from the lecture strategy and assessment aspect thus it can later improve students’ critical thinking skills.